The Development of Corporate Criminal Liability Paradigm in Environmental Pollution Cases - Febriani Mustikasari; Syaifuddin Zuhdi (Universitas Internasional Batam, 2024)
Criminal liability by corporations is a legal consequence of environmental pollution caused by the activities of the corporation itself. This research is a normative juridical research that combines statutory and comparative approaches through processing of primary, secondary, and tertiary legal materials with descriptive analysis methods. The purpose of this study is to determine the development of the paradigm and corporate criminal liability in cases of environmental pollution. The results of this study found that corporate criminal liability related to environmental pollution cases is at least regulated in Law Number 32 of 2009 (UUPPLH), the Omnibus Law, and the New Penal Code which will soon come into effect. There are differences in the provision of criminal sanctions in each law. But in general, it can be concluded that environmental pollution by corporations is a legal act that must be dealt with legally so as not to create a greater adverse impact on the environment and society.